3D Co‐Doping α‐Ni(OH)2 Nanosheets for Ultrastable, High‐Rate Ni‐Zn Battery. Issue 8 (11th December 2022) - Wang, Kaixin; Fan, Xiaoyong; Chen, Shengjie; Deng, Junkai; Zhang, Lulu; Jing, Maosen; Li, Julong; Gou, Lei; Li, Donglin; Ma, Yue
Abstract: The α‐Ni(OH)2 is regarded as one promising cathode for aqueous nickel‐zinc batteries due to its high theoretical capacity of ≈480 mAh g −1, its practical deployment however suffers from the poor stability in strong alkaline solution, intrinsic low electrical conductivity as well as the retarded ionic diffusion. Herein, a 3D (three dimensional) macroporous α‐Ni(OH)2 nanosheets with Co doping is designed through a facile and easily scalable electroless plating combined with electrodeposition strategy. The unique micrometer‐sized 3D pores come from Ni substrate and rich voids between Co‐doping α‐Ni(OH)2 nanosheets can synergistically afford facile, interconnected ionic diffusion channels, sufficient free space for accommodating its volume changes during cycling; meanwhile, the Co‐doping can stabilize the structural robustness of the α‐Ni(OH)2 in the alkaline electrolyte during cycling. Thus, the 3D α‐Ni(OH)2 shows a high capacity of 284 mAh g −1 at 0.5 mA cm −2 with an excellent retention of 78% even at 15 mA cm −2, and more than 2000 stable cycles at 6 mA cm −2, as well as the robust cycling upon various flexible batteries. This work provides a simple and efficient pathway to enhance the electrochemical performance of Ni‐Zn batteries through improving ionic transport kinetics and stabilizing crystal structure of cathodes. Abstract : A 3D porous Co‐doping α‐Ni(OH)2 nanosheets is designed through electroless plating combined with electrodeposition . The micrometer‐sized 3D pores and rich voids between nanosheets can synergistically afford facile, interconnected ionic diffusion channels, sufficient free space for accommodating volume changes; meanwhile, the Co‐doping can stabilize the structural robustness of α‐Ni(OH)2 in the alkaline electrolyte, resulting in outstanding high‐rate capacity and long‐term cyclability.